PENERAPAN MODEL PEMBELAJARAN GUIDED INTERACTIVE VISUAL SHARING (GIVS) DI PAUD KOBER AL–KHOIROOT - Brilliancessa Admyco; Chaitra, Rahmadhita; Naura Yasmina Mulia; Raissa Rizqia Athaya; Syahla Zira Ridwan; Ilma Hapita Destiani; Lesi Oktiwanti (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Early childhood education is a fundamental period in individual development that occurs between the ages of 0 and 6 years, where growth occurs in the cognitive, affective, and psychomotor aspects. However, learning practices in the field still face problems related to child participation due to the limited use of varied learning media. This study aims to develop and implement the Guided Interactive Visual Sharing (GIVS) learning model which includes Guided Learning, the use of puzzle envelopes, Picture and Picture, and Share Your Information. This study used a pre-experimental method with a quantitative approach, with a one-group pretest-posttest design. The research subjects were 18 early childhood children. Data collection techniques were carried out through observation and assessment instruments, with validity tests using Aiken’s V formula, and data analysis using the Wilcoxon test to see differences in results before and after treatment. This learning method is designed to create a participatory and child-centered learning atmosphere. The results of the study indicate that the application of the GIVS model can improve children’s understanding and participation in the learning process. Thus, the application of the GIVS model can be an innovative solution in early childhood learning to improve children’s understanding and participation.